Implementation and initial evaluation of falls risk reduction resources in a rural Native American Community - Kyle M. Knight (BMC, 2021)
Abstract Background Although falls are common and can cause serious injury to older adults, many health care facilities do not have falls prevention resources available. Falls prevention resources can reduce injury and mortality rates. Using the Centers for Disease Control and Prevention's (CDC) Stopping Elderly Accidents, Deaths & Injuries (STEADI) model, a falls risk clinic was implemented in a rural Indian Health Service (IHS) facility. Methods A Fall Risk Questionnaire was created and implemented into the Provider's Electronic Health Records system interface to streamline provider screening and referral of patients who may be at risk for falls to a group falls risk reduction class. Results Participants exhibited average improvements in the Timed Up and Go (6.8 s) (P = 0.0001), Five-Time Sit-to-Stand (5.1 s) (P = 0.0002), and Functional Reach (3.6 inches) (P = 1.0) tests as compared to their own baseline. Results were analyzed via paired t test. 71% of participants advanced out of an "increased risk for falls" category in at least one outcome measure. Of the participants to complete the clinic, all were successfully contacted and three (18%) reported one or more falls at the 90-day mark, of which one (6%) required a visit to the Emergency Department but did not require hospital admission. Conclusions In regards to reducing falls in the community, per the CDC STEADI model, an integrated approach is best. All clinicians can play a part in reducing elder falls.